2018
DOI: 10.1016/j.redox.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of mitochondria in ischemic stroke

Abstract: Stroke is the leading cause of adult disability and mortality in most developing and developed countries. The current best practices for patients with acute ischemic stroke include intravenous tissue plasminogen activator and endovascular thrombectomy for large-vessel occlusion to improve clinical outcomes. However, only a limited portion of patients receive thrombolytic therapy or endovascular treatment because the therapeutic time window after ischemic stroke is narrow. To address the current shortage of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
280
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(285 citation statements)
references
References 233 publications
(297 reference statements)
5
280
0
Order By: Relevance
“…More than 87% of strokes are ischemic and caused by obstruction of one or more cerebral arteries [1]. An inadequate supply of oxygen and glucose results in an ischemic cascade involving mitochondrial [2] and endoplasmic reticulum (ER) [3] dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 87% of strokes are ischemic and caused by obstruction of one or more cerebral arteries [1]. An inadequate supply of oxygen and glucose results in an ischemic cascade involving mitochondrial [2] and endoplasmic reticulum (ER) [3] dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The BCL-2 family has been categorized into 2 groups: anti-apoptotic proteins, including Bcl-2, Bcl-xL, and Bcl-w, and proapoptotic proteins, such as Bax, Bak, Bim, Bid, Bad, Noxa, and p53-upregulated modulator of apoptosis (PUMA) [16][17][18][19]. The pro-apoptotic BH3-only BCL-2 subfamily is known to be upregulated after cerebral ischemia [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral I/R injury is a common clinical pathophysiological phenomenon after restoring blood perfusion in stroke patients, which involves multiple pathogenesis [7]. Mitochondria reportedly play an important role in the development of I/R injury, which is involved in calcium homeostasis, oxidative phosphorylation, reactive oxygen species production, and apoptosis [13]. Recent studies have suggested that morphological changes in the mitochondria are relevant to I/R injury [8,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is considered a vital component of the development of cerebral I/R injury [30]. Excessive mitochondrial fission promotes mitochondrial outer membrane permeability and increases Cyto c release, subsequently activating the apoptotic cascade reaction and eventually aggravating neurological damage [13,31]. Moreover, in a study by Wang et al [32], adenoviral Fis1, which can induce Fis1 overexpression, increased mitochondrial fission and apoptosis, whereas Fis1 knockdown attenuated mitochondrial fission and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation